2018
DOI: 10.3390/molecules23123146
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic Co-Digestion of the Organic Fraction of Municipal Solid Wastes—The Influence of Food Industry Wastes Addition on Biogas Production in Full-Scale Operation

Abstract: Anaerobic digestion (AD) has been used widely as a form of energy recovery by biogas production from the organic fraction of municipal solid wastes (OFMSW). The aim of this study was to evaluate the effect of the introduction of co-substrates (restaurant wastes, corn whole stillage, effluents from the cleaning of chocolate transportation tanks) on the thermophilic anaerobic digestion process of the mechanically separated organic fraction of municipal solid wastes in a full-scale mechanical-biological treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…Based on that, it can be found that biogas yield per ton was slightly higher in ss-OFMSW (111.1 m 3 /ton) than for ms-OFMSW (105.3 m 3 /ton). The obtained biogas productivity was similar to the results reported in our previous study [7] and by other researchers [21,30]. Nonetheless, owing to a variety of OFMSWs, it is not easy to make a comparison of the collected results with those facilities described in Europe or other places in the world.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Based on that, it can be found that biogas yield per ton was slightly higher in ss-OFMSW (111.1 m 3 /ton) than for ms-OFMSW (105.3 m 3 /ton). The obtained biogas productivity was similar to the results reported in our previous study [7] and by other researchers [21,30]. Nonetheless, owing to a variety of OFMSWs, it is not easy to make a comparison of the collected results with those facilities described in Europe or other places in the world.…”
Section: Resultssupporting
confidence: 89%
“…Generally, the pH value ought to be between 7.2 and 7.8. It might, however, be influenced by temperature and sampling, and it might be unique to the particular facility [7,33]. During testing the ms-OFMSW AD, the pH-value was 8.5 in the inlet section, with slight growth to 8.6 in the outlet (Figure 4a), which was typical for the examined MBT plant.…”
Section: Resultsmentioning
confidence: 98%
“…The full-scale research was conducted in anaerobic digestion plant using the OFMSW with about 5% addition of restaurant waste as co-substrate in the course of 2 months. Addition of food waste was set up and limited based on the previous research results [31].…”
Section: Resultsmentioning
confidence: 99%
“…For the MSW treatment (mainly the organic fraction of municipal solid waste (OFMSW)), various methods have been applied to reduce landfilling, which is incompatible with current tendencies (e.g., circular economy, zero waste) [1]. For example, biological (anaerobic digestion [6] and composting [5]) and thermochemical (gasification [7] and hydrothermal [8]) treatments [9] have been used. Among the developed treatment pathways, anaerobic digestion (AD) has received more adherents worldwide [3,10].…”
Section: Introductionmentioning
confidence: 99%